2013
DOI: 10.1248/cpb.c13-00066
|View full text |Cite
|
Sign up to set email alerts
|

Fasudil Inhibits Epithelial-Myofibroblast Transdifferentiation of Human Renal Tubular Epithelial HK-2 Cells Induced by High Glucose

Abstract: Renal fibrosis is a crucial pathologic process underlying diabetic nephropathy (DN). Central to this process is the epithelial-mesenchymal transformation (EMT) of tubular epithelial cells. Fasudil, a Rho-associated coiled-coil forming protein serine/threonine kimase (ROCK) inhibitor, protects against renal fibrosis in a variety of renal injury models. However, fasudil's effects on renal fibrosis in DN remain unknown. The aim of the present study was to investigate the effects of fasudil on high glucose-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 41 publications
3
28
1
Order By: Relevance
“…Therefore, in our cellular model under high-glucose conditions, Arg kinase downregulation could activate the RhoA-ROCK signaling by reducing RhoA inhibition induced by p190RhoGAPA. The activation of this signaling would explain the increase of stress fibers (Hernández et al, 2004) and TGF-β1 production (Gu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, in our cellular model under high-glucose conditions, Arg kinase downregulation could activate the RhoA-ROCK signaling by reducing RhoA inhibition induced by p190RhoGAPA. The activation of this signaling would explain the increase of stress fibers (Hernández et al, 2004) and TGF-β1 production (Gu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, what is the main cellular type responsible for extracellular matrix deposition is still a matter of debate. Some studies have shown that tubular cells might undergo an in vitro epithelialmesenchymal transition (EMT) and have a direct role in tubulointerstitial fibrosis development (Lee and Han, 2010;Hills et al, 2012;Gu et al, 2013). However, conclusive evidence of a full EMT process in vivo is a controversial point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Rho GTPases (RhoA, Rac1, and Cdc42) have been implicated in the regulation of cell motility, actin cytoskeleton, and EMT [30,31]. Because emerging evidences demonstrated that treatment with rapamycin inhibited RhoA and Rac1 activity during EMT [29,33], we hypothesized that mTOR may regulate cell migration and actin reorganization in EMT of RPMCs at least in part by mediating the activity of the small GTPases.…”
Section: Rapamycin Inhibits Rpmc Migration Enhanced By Hgmentioning
confidence: 99%
“…Generally, RhoA stimulates formation of actin stress fibers and focal adhesions, Rac1 promotes formation of lamellipodia, and Cdc42 induces formation of filopodia [29]. It has been shown that Rho GTPases play important roles in EMT [30][31][32]. Further studies investigated the relationship between mTOR and Rho GTPases (RhoA, Rac1, and Cdc42) during EMT [33,34].…”
Section: Introductionmentioning
confidence: 99%